Debus Walantaka: Fenomena Budaya Banten - Isman Nasution (Antropologi Indonesia, 1997)
Debus is a cultural expression of the Bantenese which perform the invulnerability of the body against sharp things. Some scholars regard debus as a kind of performance in which the actors experience ecstasy. This folk performance conveys certain cultural meanings and values and reflect the historical background of Bantenese which marked by conflict and social symbolizes heroism, patriotism and Islam.